2018
DOI: 10.1101/385930
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heat stress modifies the lactational performances and the urinary metabolomic profile related to gastrointestinal microbiota of dairy goats

Abstract: 22 23 ¶ These authors contributed equally to this work 24 25 26 27 2 28 Abstract29 The aim of the study was to identify the candidate biomarkers of heat stress (HS) in the 30 urine of lactating dairy goats through the application of proton Nuclear Magnetic 31 Resonance ( 1 H NMR)-based metabolomic analysis. Dairy does (n = 16) in mid-lactation 32 were submitted to thermal neutral (TN; indoors; 15 to 20°C; 40 to 45% humidity) or HS 33 (climatic chamber; 37°C day, 30°C night; 40% humidity) conditions according t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Microbiome sequencing was used to determine changes in the rumen bacterial taxa of Jersey and Holstein cows to heat stress [14]. Several experiments have already been conducted to measure some metabolites of heat stress in dairy goats [15], pigs [16] and dairy cows [17]. In addition, Tian [18] reported 10 biomarkers in milk associated with heat stress-induced metabolomic alterations in blood.…”
Section: Introductionmentioning
confidence: 99%
“…Microbiome sequencing was used to determine changes in the rumen bacterial taxa of Jersey and Holstein cows to heat stress [14]. Several experiments have already been conducted to measure some metabolites of heat stress in dairy goats [15], pigs [16] and dairy cows [17]. In addition, Tian [18] reported 10 biomarkers in milk associated with heat stress-induced metabolomic alterations in blood.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of NFkB pathway increases tight junction permeability through expression changes of claudins in the mammary gland 37 . The higher losses of milk lactose detected in HS-LPS can be explained by greater tight junction leakiness, since HS has been shown to compromise tight junction integrity in other tissues such as the gastrointestinal barrier 9,38 .…”
Section: Responses To Intramammary Lps Challenge Under Thermo-neutralmentioning
confidence: 99%
“…HS causes profound changes in the gut microbiota structure of primiparous sows, especially in the abundance and diversity of some SCFA-producing species ( Singh et al., 2019 ). Many studies conducted on other animals, including broiler chickens ( Wang et al., 2018a ), goats ( Contreras-Jodar et al., 2019 ), ducks ( He et al., 2019 ), and dairy cows ( Chen et al., 2018 ), have also shown that HS affected the composition of the gut microbiota. However, the alteration in the gut microbiota composition and its association with physiological changes induced by HS in pigs has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%